A Study of the Impact or Effect of Information Technology on Hrd In Company or Organization: The Transformation of HR Practices in the Digital Age (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Computers havesimplified the task of analyzing vast amounts of data, and they can beinvaluable aids in HR management, from payroll processing to record retention.With computer hardware, software, and databases, organizations can keep recordsand information better, as well as retrieve them with greater ease. InformationTechnology (IT) as a structural factor and instrument transforms architect oforganizations, business processes and communication and is increasinglyintegrated into Human Resource Management. While IT has impacts on HR at thesame time managers, employees, customers and suppliers increase theirexpectancies for HR functions. The importance of knowledge and human capitalmake extra suppression on HR functions and new competencies for HRprofessionals are expected. With the arrival of information technology, humanresource management practices are changed.